An automatic method for generating carbon nanostructure atomistic models using hexagonal meshes with properly distributed defects. (19th October 2016) - Shang, Feifei; Zeng, Zhen; Liu, Jianfei; Chen, Tingfei
Summary: Atomistic models, which are crucial for performing molecular dynamics simulations of carbon nanostructures, consist of virtual hexagonal meshes with defects properly distributed in the intersectional areas. Currently, atomistic models are created mostly by hand, which is a notably tedious and time‐consuming process. In this paper, we develop a method that produces atomistic models automatically. Because a hexagonal mesh and triangulation represent dual graphs, our work focuses on the creation of proper triangulation. The edge lengths of the triangulation should be compatible with the lengths of the C–C bonds, and vertices with valences other than 6 (due to the defects in the hexagonal mesh) should be properly arranged around the boundaries of the different components of a carbon nanostructure. Two techniques play important roles in our method: (1) sphere packing is used to place the nodes for triangulation that produces nearly constant edge lengths of the triangles and (2) the movement and editing of defects is used to control the number and positions of the defects. We subsequently develop a computer program based on this method that can create models much easier and faster than the current handwork method, thereby reducing the operation time significantly. Copyright © 2016 John Wiley & Sons, Ltd.